Policy analysis and advocacy for livestock-based development: The gap between household-level analysis and higher-level models - Baker, Derek; Enahoro, Dolapo K. (Elsevier, 2014)
The dichotomy in approaches to policy analysis for developing countries’ livestock sectors is presented. Substantial experience and information generated from a large number of household-level studies is not being utilised by macro- and aggregate models which fail to recognise heterogeneity, dynamics and fundamental drivers of change in livestock systems. Household-level studies are not standardised and rarely identify and characterise key drivers and mechanisms for exploiting heterogeneity in policy analysis. The paper provides an overview of a set of six papers contained in a special edition which define and address this gap in analytical approaches and identify aspects of the way forward. Evidence is presented of inconsistencies and practicalities which emphasise the gap, but all papers present evidence of integrative progress and list opportunities for accelerating it. Constraints on the subject matter are outlined and a challenge to livestock policy analysts is made.